Camino de una universidad virtual para convertirse en un nodo de conocimiento abierto: El caso de la UOC - Xarles-i-Jubany, Gemma; Aguilera-Caballero, Begona; Llueca, Ciro; Martínez-Samper, Pastora (Revista Científica, 2023)
In November 2021, UNESCO approved its Recommendation on open science, whose implementation makes it possible to incorporate “open culture” into any international, national, regional, or institutional policy related to information or research. The recommendation explicitly recognizes open science as a requirement for leaving no one behind with regard to access to academic knowledge and the benefits of scientific progress. This same conviction led the UOC to elaborate its own Open knowledge action plan in 2018. This Plan, with a time horizon extending until 2030, constitutes the roadmap and institutional proposal of the UOC to become a hub for open and global knowledge, thus contributing to fulfilling the Sustainable Development Goals set by the United Nations' 2030 Agenda. In its fifth year of implementation, and with eight more years to go, in this article, we share the preliminary results of the process and reflect upon the way in which its implementation helps the University to become a global knowledge hub with a greater social impact. All this, based on the particularity of being a Plan adopted by and for a fully online university.